Practical Demonstration Strategy and Motor Coordination in Volleyball Skills: Strategi Demonstrasi Praktis dan Koordinasi Motorik dalam Keterampilan Bola Voli - Sakhi, Rouaa Abdullah (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Teaching volleyball effectively requires strategies that integrate visual, motor, and cognitive engagement. Specific Background: Practical demonstration enables learners to connect observation with movement, promoting better psychomotor learning outcomes. Knowledge Gap: Few studies have examined how demonstration-based strategies improve both coordination and technical serving skills among students. Aims: This study aimed to determine the effectiveness of the practical demonstration strategy in developing motor coordination and serving skills in volleyball. Results: Findings revealed significant improvements in coordination and serving accuracy for students exposed to the demonstration strategy compared with the control group. Novelty: The study introduces an integrated visual–motor approach in volleyball education. Implications: The results highlight that combining visual modeling with physical execution enhances learning efficiency and can be applied across various physical education settings. Highlights:• Practical demonstration improves motor coordination and serving performance.• Visual–motor learning enhances psychomotor skill development.• The strategy supports modern constructivist approaches in sports education. Keywords:Practical Demonstration, Motor Coordination, Volleyball, Serving Skills, Physical Education